2012
DOI: 10.1111/j.1475-6773.2012.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Standard versus Patient‐Centered Collaborative Care Interventions for Depression among African Americans in Primary Care Settings: The BRIDGE Study

Abstract: Objective. To compare the effectiveness of standard and patient-centered, culturally tailored collaborative care (CC) interventions for African American patients with major depressive disorder (MDD) over 12 months of follow-up. Data Sources/Study Setting. Twenty-seven primary care clinicians and 132 African American patients with MDD in urban community-based practices in Maryland and Delaware. Study Design. Cluster randomized trial with patient-level, intent-to-treat analyses. Data Collection/Extraction Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 56 publications
0
65
0
Order By: Relevance
“…Specifically, the numerator consists of certain parent codes (all questions, psychosocial and lifestyle information and emotional talk) plus medical team codes (psychosocial and lifestyle questions, psychosocial and lifestyle information and counselling, emotionally responsive statements, partnering and activation statements). The denominator includes certain parent codes (medical information and questions) plus medical team codes (medical and therapeutic regimen information and counselling; medical questions; instructions and orientation (34, 35). …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the numerator consists of certain parent codes (all questions, psychosocial and lifestyle information and emotional talk) plus medical team codes (psychosocial and lifestyle questions, psychosocial and lifestyle information and counselling, emotionally responsive statements, partnering and activation statements). The denominator includes certain parent codes (medical information and questions) plus medical team codes (medical and therapeutic regimen information and counselling; medical questions; instructions and orientation (34, 35). …”
Section: Methodsmentioning
confidence: 99%
“…A recent trial enhancing collaborations between community agencies and the health care system improved depression outcomes in predominantly minority (46% African-American, 41% Latino) safety-net clients 44. The BRIDGE trial showed that standard CC and patient-centered culturally adapted CC had similar benefits on depression outcomes in African-American patients, although patient satisfaction was greater in those receiving the culturally adapted approach 46. Another trial found that six telepsychiatry sessions provided by a bilingual psychiatrist to low-income Hispanic primary care patients was superior to usual care in improving depression outcomes 47.…”
Section: Added Benefits For Minority Underserved and Other Vulnerabmentioning
confidence: 99%
“…Balint first described PCC as “understanding the patient as a unique human being.” During the 20th century, PCC became a focus of healthcare systems with its promise to increase patient satisfaction and improve outcomes . A growing body of evidence has linked PCC practices with improvements in a variety of health conditions, increased adherence, decreased healthcare utilization, better ratings of care and improved quality of care . By 2001, The Institute of Medicine identified PCC as a key aspect of high‐quality care .…”
Section: Introductionmentioning
confidence: 99%